PENGARUH KUALITAS LAYANAN DAN WORD OF MOUTH MELALUI MINAT TERHADAP KEPUTUSAN NASABAH DALAM MENGGUNAKAN E-BANKING PADA BANK BNI - Eka Dyah Setyaningsih (Universitas Gunadarma, 2017)
Electronic banking is a prayer One means of Banking to review financial transactions facilitate kita hearts. The Purpose Of The study is to review Test how influence Of SERVICE QUALITY And word of mouth through the use of Decision Against Interests e-banking of Bank BNI. Sample Research Singer WITH using 330 respondents and is the object of research Namely Bank e-banking users BNI. The sampling technique used snowball sampling. Research models using Structural Equation Modelling (SEM) WITH QUALITY OF SERVICE (X1) And the word of mouth communication (X2) as well as the free variable interest (Y1) and Decree (Y2) as a variable prepaid NOT free. Processing of the findings of statistical tools AMOS. The results of his research is QUALITY SERVICE WITH positive effect Decision Against Customers using e-banking hearts Correlation Values for 0,206 and the communication of positive word of mouth influence the Customer Decision Against WITH Correlation Value for 0,208 Keywords: quality of service, word of mouth, customer interest, customer's decision